The Ponseti method for the treatment of congenital club foot: review of the current literature and treatment recommendations - Radler, Christof (Springer Berlin Heidelberg, 2013)
The Ponseti method has become the gold standard of care for the treatment of congenital club foot. Despite numerous articles in MEDLINE reporting results from around the globe there are still crucial details of the Ponseti method which seem to be less commonly known or considered. The Ponseti method is not only a detailed method of manipulation and casting but also of preventing and treating relapse. Recommendations on how to correct complex club foot have resulted in an almost 100 % initial correction rate. The foot abduction brace is crucial for preventing relapse and is still a challenge for families and sometimes doctors alike. Experience and knowledge on how to support the parents, how to set and apply the brace in the best possible way and how to solve problems that can be encountered during the bracing period are essential to ensure compliance. Regular follow-up visits are necessary to be able to detect early signs of recurrence and prevent full relapse by enforcing abduction bracing, recasting or performing tibialis anterior tendon transfer. Recent midterm outcome studies have shown that by following the Ponseti treatment regime in all aspects it is possible to prevent open joint surgery in almost all cases. The body of literature of the last decade has evaluated many steps and aspects of the Ponseti method and gives valuable answers to questions encountered in daily practice. This review of the current literature and recommendations on the different aspects of the Ponseti method aims to promote understanding of the treatment regime and its’ details.